Pengembangan Modul Berpendekatan Pembelajaran Science Technology Engineering And Mathematic Pada Materi Keanekaragaman Hayati Untuk Meningkatkan Kreativitas: (Module Development Approaching Science Technology Engineering And Mathematical Learning on Biodiversity Materials to Increase Creativity) - Agung Laksono; M. Rusdi; Tedjo Sukmono (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Module development is a process of developing procedural knowledge in creating meaningful learning. Learning is developed to obtain multidisciplinary learning, student-centered, active and critical, changes in interactive learning patterns. In the learning process with a STEM approach, information is formed through collaboration and creativity. Students use skills and learning processes in science, technology, engineering, and mathematics in their thinking processes to solve problems. This development aims to determine procedures, designs, student responses and teacher assessments in increasing creativity. Development of the biodiversity module with the STEM approach using the Project Based Learning model on biodiversity material in SMA Negeri 2 Jambi City by adapting the ADDIE model. The research instruments used were interview sheets, open and closed questionnaires, and a daily log. The product developed is a Biodiversity Module with a STEM approach. The module was validated by three teams of experts and declared feasible then the teacher's assessment had a kappa value of 0.74 in a good category. The results of one-on-one trials for project one have a percentage of 82.08% in the category of